Peningkatan Hasil Belajar Matematika Melalui Penerapan Pembelajaran Model Problem Based Learning (PBL) Pada Siswa Kelas XII SMKN 1 Kalitengah - Halim, Abdul (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2020)
This study aims to determine the occurrence of increasing student learning outcomes through the application of probem based learning (PBL) models. This type of research is Classroom Action Research (CAR) with two cycles. This research was conducted at SMKN 1 Kalitengah Lamongan in the odd semester of the 2019/2020 school year. The subjects of this study were students of class XII Multimedia at SMKN 1 Kalitengah which consisted of 30 students. The variables in this study consisted of the independent variable, namely the application of the Problem Based Learning model and the dependent variable, namely the learning outcomes of mathematics. The research instrument consists of learning tools. Observation sheets (observations) and mathematics learning outcomes tests. Learning devices are used as a reference for the implementation of learning, observation sheets are used to observe teacher and student activities. Learning outcomes test is used to measure the achievement of learning outcomes achieved by students. The data analysis technique used comparative descriptive in the form of percentages or descriptive statistics from the results of learning mathematics in each cycle. Based on the results of the study, it can be concluded that the Problem Based Learning (PBL) model can improve learning outcomes. This can be seen from the learning outcomes in the first cycle to achieve classical learning completeness, namely 53%, namely only 16 students from 30 students completed learning individually and increased in cycle II, namely 27 students from 30 students or 90% students have completed individual studies. with KKM 75. Likewise, teacher and student activities, namely teacher activities in the first cycle obtained an average score of 2.94 or only 59% and in the fairly good category, increased in the second cycle, which reached an average score of 4.06 and included in the good category. The average score of student activity in the first cycle was 2.8 or only 56% and showed that in the fairly good category it increased in the second cycle, namely 3.8 and included in the good category. Because learning with Problem Based Learning models can increase student activity and also improve learning outcomes in mathematics subjects. Thus, the problem based learning (PBL) model can be applied as an alternative in learning.